BOARDS OF MANAGEMENT SUPERVISORY PRACTICES AND STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN KIPKOMO SUB COUNTY, KENYA - Wafula , Christine N. V.; Chepkoech, Emily; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
The quality of management especially at secondary level is and continues to be a major concern of the government of Kenya. In the world, the school governing bodies are the external managers of the schools and are expected to be in constant touch with school, students, and teachers as well as with other stakeholders. The purpose of this study was to assess the influence Boards of Management (BOM) supervisory practice on students’ academic performance in public secondary schools in Kipkomo Sub County, Kenya. The study adopted descriptive research design with a target population of 962 persons comprised of 32 school principals, 642 teachers, and 288 BOM members. The study adopted a stratified random sampling technique and sample size of 278 determined using Krejcie and Morgan table (1970). The study used structured questionnaires and interview guides as the main tools of data collection. The instrument was validated by the experts in the area of study. The reliability of the instrument was determined through a pilot study in the neighbouring Trans Nzoia East Sub-County. Thereafter, Cronbach alpha coefficient of 0.79 was obtained from the instrument. This indicated that the instrument was reliable. Quantitative data was analyzed using descriptive statistics and presented in tables, while qualitative data was analyzed according to the themes based on research questions and the objectives and thereafter, inferences and conclusions drawn. The study will benefit the academicians, policymakers, and community members. The study concluded that BOM’s supervisory practices influence students̕ academic performance in public secondary schools. It was recommended that the policy makers and community should consider Boards of Management Governance practices such as BOM’s supervisory practices when working towards improving students̕ academic performance in public secondary schools.